Preventing Crime and Poor Health Among Aboriginal People: The Potential for Preventative Programming - Monchalin, Lisa; Marques, Olga (First Peoples Child & Family Review, 2013)
The purpose of this paper is to examine prevention programs, and discuss their potential for having an impact on reducing crime and poor health outcomes for Aboriginal people. A historical context is first outlined in order to provide a context for understanding the disproportionate amount of crime and related poor health outcomes affecting Aboriginal people. Risk factors for crime and health are identified, demonstrating their interrelatedness and overlapping nature, indicating that risk factors do not existing in isolation from each other. Existing crime prevention programs are subsequently discussed, paying particular attention to the intersection between evidence-based outcomes and programs offered at Aboriginal Friendship Centres. The use of prevention programs for preventing/reducing crime and related health costs (i.e. substance use/abuse, smoking, and/or addictions) has been positively established by existing research. Thus, it is suggested that these programs offered in Aboriginal centres, such as Aboriginal Friendship Centres, should be furtherexpanded and supported.